Guiding principles for developing initiatives to prevent child sexual abuse material offending - Gannoni, Alexandra (Trends & issues in crime and criminal justice, 2024)
This study sought to identify principles to guide the development and implementation of initiatives that aim to prevent child sexual abuse material (CSAM) offending. It did so through a review of research on the implementation and effectiveness of initiatives that aim to prevent CSAM offending, and through input from an international expert advisory group. Seven principles are described in this paper: the use of advertising campaigns; confidentiality and anonymity; an empathetic and non-judgemental approach; accessibility; training and support; tailored programs; and evaluation. These broad principles can act as a valuable resource for practitioners and policymakers.